PERFORMANSI INSTALASI PENGOLAH AIR LIMBAH TAMBAK SUPERINTENSIF - Rachman Syah; Mat Fahrur; Hidayat Suryanto Suwoyo; Makmur Makmur (Media Akuakultur, 2017)
Pengolahan air buangan tambak superintensif (TSI) adalah usaha untuk mengurangi beban bahan pencemar yang terkandung di dalam air buangan TSI sehingga aman dan tidak membahayakan saat dibuang ke lingkungan. Penelitian ini bertujuan untuk mengevaluasi desain dan performansi Instalasi Pengolahan Air Limbah (IPAL) dalam memperbaiki kualitas air buangan TSI sebelum dibuang ke badan air. IPAL terdiri atas kolam sedimentasi, dua kolam aerasi, dan satu kolam penampungan. Ke dalam kolam penampungan ditebari ikan mujair serta rumput laut Gracilaria sp. yang dibudidayakan dengan metode long line, berfungsi sebagai biokontrol. Sampel air diambil di bagian inlet IPAL, oulet kolam sedimentasi atau inlet kolam aerasi-1, outlet kolam aerasi-1 atau inlet kolam aerasi-2, outlet kolam aerasi-2 atau inlet kolam penampungan, serta outlet kolam penampungan, setiap dua minggu selama 105 hari pemeliharaan. Parameter yang diukur adalah total padatan tersuspensi (TSS), total amonia nitrogen (TAN), nitrit, nitrat, fosfat, bahan organik terlarut (BOT), dan biological oxygen demand (BOD-5). Spesifikasi teknis IPAL yang diamati meliputi ukuran dan volume IPAL, volume dan waktu tinggal air buangan tambak, dan efisiensi kinerja IPAL, serta rasio volume IPAL dan volume total air tambak. Hasil penelitian menunjukkan bahwa IPAL dapat mengurangi beban bahan pencemar dengan tingkat efisiensi antara 53,1%-99,4%; namun masih diperlukan peningkatan kapasitas dalam mengurangi konsentrasi BOT. IPAL menghasilkan efisiensi yang tinggi terhadap TSS, TAN, nitrit, Total Nitrogen (TN), dan fosfat. Rasio volume IPAL dan volume air tambak 30:70 dengan waktu tinggal minimal lima hari, dapat dijadikan acuan dalam pembangunan IPAL tambak superintensif.A wastewater treatment plant (WTP) in a super-intensive shrimp farm is used to reduce organic matters contained in super-intensive shrimp farm effluent. Through the WTP, the waste water from shrimp facilities can safely and harmlessly be released to the receiving environments. The aims of this study were to evaluate the design and performance of a WTP in reconditioning waste water released from a super-intensive shrimp farm prior to release to water bodies. The WTP was made of a series of sedimentation pond, two aeration ponds, and one reservoir or equalitation pond. The tilapia fish and seaweed, Gracilaria sp., were stocked in the equalitation pond where the seaweed was cultured using long line method; these organisms were used as bio-control. Water samples were collected fortnightly during 105 days of culturing duration from the WTP inlet, outlet of sedimentation pond or at inlet of the first aeration pond; outlet of the first aeration pond or inlet of the second aeration pond, outlet of the second aeration pond or inlet of equalitation pond and the outlet of equalitation pond. The measured variables were total suspended solid (TSS), total ammonia nitrogen (TAN), nitrite, nitrate, phosphate, total organic matters (TOM), and five days biological oxygen demand (BOD5). The evaluated technical performances of the plant were its size and volume; volume and retention time of effluent, efficiency of WTP performance and volume ratios of the WTP and total volume of shrimp pond. The results of the study indicated that the WTP was able to reduce concentrations of nutrients and solids in effluent by 53.1%-99.4% of efficiency. However, its capacity need to be increased due to reducing concentrations of TOM. The WTP was highly efficient in reducing the concentrations of TSS, TAN, nitrite, total N, and phosphate. The volume ratios between the plant and pond waters were 30:70 with minimum retention time five which days could be proposed for wastewater treatment pond for super-intensive shrimp ponds.